2013
DOI: 10.1111/pan.12260
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative emergence delirium in pediatric patients undergoing cataract surgery – a comparison of desflurane and sevoflurane

Abstract: Emergence delirium (ED) after desflurane and sevoflurane anesthesia was comparable using a validated PAED scale in pediatric cataract surgery. There was no correlation between preoperative anxiety and ED in these children; however, children with higher pain scores were more likely to have a higher ED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 24 publications
3
31
1
1
Order By: Relevance
“…16,17 Our results are consistent with these findings despite the fact that these previous studies differed in their use of nitrous oxide for anesthesia induction and maintenance. Nevertheless, few studies have compared anesthesia emergence times between desflurane and sevoflurane after volatile induction in adults.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…16,17 Our results are consistent with these findings despite the fact that these previous studies differed in their use of nitrous oxide for anesthesia induction and maintenance. Nevertheless, few studies have compared anesthesia emergence times between desflurane and sevoflurane after volatile induction in adults.…”
Section: Discussionsupporting
confidence: 83%
“…This is most likely due to the young age of the participants in prior studies, which prevented precise measurements of recovery times. 16,17 The times in our study from discontinuation of volatile anesthetics to orientation to the patients' full name, date, and place were significantly shorter in the desflurane group than in the sevoflurane group, which suggests that changing from sevoflurane to desflurane permits faster recovery than sevoflurane anesthesia, even after sevoflurane induction. In addition, the time trend in recovery events differed between the two groups.…”
Section: Discussionmentioning
confidence: 72%
“…The literature has shown both supporting 5,7 and contradicting evidence 8,9 for an association between preoperative agitation and postoperative delirium. In the analysis we found a strong association between significant preoperative agitation and postoperative delirium (OR 3.54 95% CI 1.55-8.09: p = 0.003).…”
Section: Deliriummentioning
confidence: 99%
“…The association between agitation at induction and emergence delirium has not been clearly delineated with contradictory results being reported. [5][6][7][8][9] The incidence of POV in children has been reported as 34%.10 While preoperative anxiety and agitation have been implicated as possible risk factors for postoperative nausea and vomiting (PONV) in adults, [11][12][13][14][15] its role as a risk factor in children remains unclear. 16,17 Further, local South African data have suggested that adult African patients have a lower incidence of PONV than non-African patients 18 but no such association has yet been shown in children.…”
Section: Introductionmentioning
confidence: 99%
“…These adverse effects can cause sympathetic hyperactivity, prolonged hospital stay, and decreased patient satisfaction. Sethi et al [11] reported that the occurrence of emergence agitation in pediatric patients was not significantly different between sevoflurane and desflurane. We hypothesized that desflurane may cause more emergence delirium if it is caused by rapid recovery, but desflurane maintenance after sevoflurane induction can provide gentle induction and rapid emergence while minimizing cardiovascular changes during induction.…”
Section: Introductionmentioning
confidence: 99%